Рекреаційно-туристичний потенціал малих курортів Львівської області в період воєнного стану: особливості використання і перспективи = Recreational and tourist potential of small resorts in the Lviv oblast during martial law: features of use and prospects : ст. - Періг, Т. В.; Кушнір, Л. П.; Терлецька, О. В. (Львівський національний університет ветеринарної медицини та біотехнологій імені С. З. Ґжицького, 2024)
У статті проаналізовано особливості використання рекреаційно-туристичного потенціалу малих курортів Львівської області в період військового стану, а також можливості та перспективи їхнього розвитку як туристичних центрів. Для аналізу обрано шість селищ і сіл регіону: Брюховичі, Великий Любінь, Модричі, Немирів, Розлуч, Шкло. Здійснено загальний огляд малих курортних поселень Львівської області, з акцентом на їх розташуванні в системі розселення; проаналізовано і порівняно бальнеологічні ресурси, інші складники рекреаційно-туристичного потенціалу малих курортів, а також їхню відпочинкову інфраструктуру; досліджено вплив воєнного стану, запровадженого внаслідок російської агресії; охарактеризовано вплив реформи адміністративного територіального устрою України на майбутній розвиток малих курортів регіону. Для кожного з малих курортів встановлено перспективні сценарії розвитку як туристичних центрів з огляду на особливості розташування, фінансові можливості територіальних громад, а також наявний рекреаційно-туристичний потенціал та інфраструктуру = The article analyzes the features of using the recreational and tourist potential of small resorts in the Lviv region during martial law, as well as the opportunities and prospects for their development as tourist centers. Six villages and settlements in the region were selected for analysis: Bryukhovychi, Velykyi Lyubin, Modrychi, Nemyriv, Rozluch, and Shklo. A general overview of the small resort settlements of the Lviv region was carried out, with an emphasis on their location in the settlement system; balneological resources, other components of the recreational and tourist potential of small resorts, as well as their recreational infrastructure, were analyzed and compared; the impact of martial law, introduced as a result of Russian aggression, was studied; the impact of the administrative-territorial reform of Ukraine on the future development of small resorts in the region was characterized. For each of the small resorts, prospective development scenarios as tourist centers were established, taking into account the specifics of their location, the financial capabilities of territorial communities, as well as the existing recreational and tourist potential and infrastructure. For the settlement of Bryukhovychi, located in the suburban zone of Lviv, the optimal development would be as a full-fledged recreational and health center for Lviv residents, that is, to restore the function it previously performed. Velykyi Lyubin should develop the recreational and tourist specialization of the entire Velykolubinsky community, not just the settlement, based not only on the resources of the balneological resort but also on the numerous natural and historical-cultural monuments of all the settlements that are part of it. Nemyriv needs expansion and reconstruction of the material and technical base while maintaining its profile. The future of Rozluch is to develop based on attracting private investments, reviving the former pre-war glory of the resort, not only as a balneological but also as a ski resort. Modrychi should develop as a satellite resort of Truskavets. The development of the small resort of Shklo depends on the decisions of the central authorities regarding the subordination of the sanatorium located there.
Keywords: курорти; туристично-рекреаційна галузь; бальнеологічні ресурси; resort; recreational and tourist potential; balneological resources